Echinorhynchus trachyrinci n. sp. (Acanthocephala: Echinorhynchidae) from macrourid fishes of the northeast Atlantic - Wayland, M. T.; Gibson, D. I.; Sommerville, C. (Systematic Parasitology, 1997)
Echinorhynchus trachyrinci n. sp. (Palaeacanthocephala: Echinorhynchidae) is described from Trachyrincus scabrus (Rafinesque) (Macrouridae: Trachyrincinae) (type-host) and T. murrayi Günther from the northeast Atlantic. The most important diagnostic features of this species are: the number of longitudinal rows of hooks 17–22; the number of hooks per row 17–22+; the maximum length of hook blade 38–52µm; the proboscis width 139–224µm; and the proboscis length to width ratio 3.9–6.4:1. E. trachyrinci n. sp. is differentiated from E. gadi, E. malacocephali, E. longiproboscis, E. petrotschenkoi, E. melanoglaeae, E. theragrae and E. sebastolobi. Metechinorhynchus malacocephali Parukhin, 1985 is transferred to Echinorhynchus as E. malacocephali n. comb